Dipole-mode and scissors-mode oscillations of a dipolar supersolid - Young-S, Luis E.; Adhikari, S. K. [UNESP] (American Physical Society (APS), 2023)
We study dipole-mode and scissors-mode oscillations of a harmonically trapped dipolar supersolid, composed of dipolar droplets arranged on a one-dimensional (1D) or a 2D lattice, to establish the robustness of its crystalline structure under translation and rotation, using a beyond-mean-field model including a Lee-Huang-Yang interaction. The dipolar atoms are polarized in the z direction with the supersolid crystalline structure lying in the x-y plane. A stable dipole-mode oscillation is possible in the case of both quasi-1D and quasi-2D dipolar supersolids, whereas a sustained angular scissors-mode oscillation is possible only in the case of a quasi-1D dipolar supersolid between a maximum and a minimum of trap anisotropy in the x-y plane. In both cases there is no visible deformation of the crystalline structure of the dipolar supersolid during the oscillation. The theoretical estimate of the scissors-mode-oscillation frequency is in good agreement with the present results and the agreement improves with an increase in the number of droplets in the supersolid and also with an increase in the confining trap frequencies. The results of this study can be tested experimentally with present knowhow.